TEACH WHAT NEED TO BE TAUGHT FOR BETTER STUDENT ENGLISH SPEAKING SKILL - Wahyu Teri Aripin (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
English has been taught to student in Indonesia barely in early age. Mostly student get their first English material in elementary school at their 7 years of age. The purpose of giving that such material in the early age is to enable them to communicate in English both speaking and writing. After years of learning English, it is strange to find most of high school student in Indonesia can’t speak and write English well. At the same time, to make it even stranger, it is also found that most of their report score for English are high. According to the observation that has been conducted since 2008, it is found that material that has been delivered in English class is not what in need for student basic communication skill. Thus, what has been learned, has not been used in their daily activities. Instead student will memorize it for the sake of examination. To solve that problem, English speaking teaching model will be discussed. This model has been implemented in MAN 2 Tasikmalaya since 2013. 77,5% percent of the student participating that testing teaching model was succeeded to have good English speaking skill. The rest 22,5% fall below standard measurement.